2013
DOI: 10.1111/1469-0691.12096
|View full text |Cite
|
Sign up to set email alerts
|

Can microbiologists help to assess catheter involvement in candidaemic patients before removal?

Abstract: We compared the efficacy of three techniques--minimal time to positivity (MTTP) of blood cultures (BCs), differential time to positivity (DTTP) of BCs obtained from the catheter and peripheral veins and the number of positive BCs--in predicting catheter involvement in patients with well-demonstrated catheter-related candidaemia (C-RC) and non-catheter-related candidaemia (NC-RC).C-RC was defined as isolation of the same Candida species from blood and catheter tip culture (≥15 cfu/plate). A ROC curve was create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
51
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 27 publications
3
51
1
Order By: Relevance
“…For other Candida species, however, the sensitivity and specificity of a DTP of Ն120 min were 89% and 90%, respectively. In this study, the TTP of C. glabrata was significantly longer than those of other Candida species, consistent with the results of previous studies (10)(11)(12). Because of the longer TTP for C. glabrata, we hypothesized that the optimal DTP cutoff for C. glabrata might be longer than that of other Candida species.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For other Candida species, however, the sensitivity and specificity of a DTP of Ն120 min were 89% and 90%, respectively. In this study, the TTP of C. glabrata was significantly longer than those of other Candida species, consistent with the results of previous studies (10)(11)(12). Because of the longer TTP for C. glabrata, we hypothesized that the optimal DTP cutoff for C. glabrata might be longer than that of other Candida species.…”
Section: Discussionsupporting
confidence: 91%
“…Ben-Ami et al (11) reported that a TTP in the peripheral blood of Ն30 h ruled out the CVC as the source of candidemia (a TTP of Յ30 h displayed a sensitivity and specificity of 100% and 51%, respectively, for detecting definite CRC), but most patients in that study were nonneutropenic (11). The diagnostic performance of TTP among neutropenic patients may differ from that among nonneutropenic patients because of the higher proportion of C. tropicalis coming from the gastrointestinal tract in neutropenic patients (21) and the shorter TTP of C. tropicalis (10)(11)(12). Further studies with a large number of neutropenic patients should be performed to evaluate this issue.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This, particularly, represents a big problem in the neonatal population and in patients whose catheters have persistent occlusion. Moreover, the application of DTTP evaluation for catheter-related candidemia has not been already established (34,35). Therefore, the use of a rapid and easy-to-perform technique such as superficial culture analysis may allow us to solve these problems.…”
Section: Discussionmentioning
confidence: 99%
“…The ROC curve methodology was first developed in the 1950s for signal analysis and has been frequently used since than also for the assessment of the accuracy of medical imaging devices (17,18). Over the years, ROC curve analysis has also been increasingly applied for evaluation of microbiological diagnostic tests (19)(20)(21)(22). In this …”
mentioning
confidence: 99%